2017
DOI: 10.1111/dewb.12177
|View full text |Cite
|
Sign up to set email alerts
|

Models for truth‐telling in physician‐patient encounters: What can we learn from Yoruba concept of Ooto?

Abstract: Empirical studies have now established that many patients make clinical decisions based on models other than Anglo American model of truth-telling and patient autonomy. Some scholars also add that current medical ethics frameworks and recent proposals for enhancing communication in health professional-patient relationship have not adequately accommodated these models. In certain clinical contexts where health professional and patients are motivated by significant cultural and religious values, these current fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Preferences and values about access to and receipt of information also influence how healthcare professionals give information to parents. It has been shown that some people do not want to hear some information, especially information that has a negative element in it,33 38 parents need to be neither completely hopeful nor completely hopeless when receiving information,1 and preparation for receiving medical information should be considered because sometimes expressing this information may harm the mental health of the person 33 39. These findings are consistent with those of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Preferences and values about access to and receipt of information also influence how healthcare professionals give information to parents. It has been shown that some people do not want to hear some information, especially information that has a negative element in it,33 38 parents need to be neither completely hopeful nor completely hopeless when receiving information,1 and preparation for receiving medical information should be considered because sometimes expressing this information may harm the mental health of the person 33 39. These findings are consistent with those of this study.…”
Section: Discussionsupporting
confidence: 91%
“… 32 From the nursing leader’s perspective, this was the preferred option, as it maintains the nurse-patient therapeutic relationship of trust and good communication. 33 Also to be considered are the ethical issues widely referred to in medical ethics as outlined by Benn and Boyd: the individual autonomy of people, beneficence, non-maleficence and justice. 32 The principles of autonomy and beneficence are more concerned with individual ethics, whereas justice focuses on social ethics and the formulation of criteria for solving potential conflicts between people.…”
Section: Ethic Issues and Analysismentioning
confidence: 99%
“…In different studies [4][5][6][7], I have shown that the above engagement is not only desirable, but possible. In one study Ewuoso [4], I showed how a particular African ethics may be used to address the ethical impasse created by applying coercion in psychiatric care.…”
Section: Opinionmentioning
confidence: 99%